A efetividade dos direitos humanos diante das limitações do saber jurídico: uma reflexão sobre o diálogo judicial e interdisciplinar a partir do julgamento do caso das células-tronco embrionárias (adi nº. 3.510/2005) - Alves Neto, Josias Ferreira (2015)
Judgments about human rights require democratic environments to be incurred. The dialogue between the various stakeholders proves to be essential to overcome the limits of legal cognition so that judicial decision will be more effective as the addressed participate to it. In this sense, the unconstitutionality lawsuit n. 3.510 from 2005 shows an interesting example of operation of the dialog field since admitted in its decision making process, the presence of civil society through the amicus curiae institute and the public hearings. The mainstreaming of research on embryonic stem cells has awakened interest of several organizations that would volunteer themselves to expand the legal cognition about the beginning of life. It has been presented arguments of medical, biological, sociological, historical ordinations and some others arguments to uncover the web of bonds involving the constitutional subject matter. The judges interacted with such argumentative space in order to make the final decision about the constitutionality of scientific research from the influence of the miscellaneous views that were presented about the subject. Thus, there was an interaction field between juridical and extrajuridical knowledge in the human rights treatment that, from the perspective of this study, contributed to the construction of the final text of the judgment.